KESIAPSIAGAAN BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN LEMBATA DALAM PENANGANAN BENCANA ALAM DI KABUPATEN LEMBATA - Carles Bay Koda; Urbanus Ola; Veronika Ina Assan Boro (Journal Education and Government Wiyata, 2025)
This research is titled "The Preparedness of the Regional Disaster Management Agency (BPBD) in Disaster Management in Lembata Regency." The research problem addressed in this thesis is: How is the preparedness of the Regional Disaster Management Agency (BPBD) in disaster management in Lembata Regency? The theories used in this study are Agile Governance and Agile Governance in Disaster Preparedness. Primary data sources include informants, while secondary data consists of documents related to the research variables. Data collection techniques used are interviews, observation, and documentation. Data analysis was conducted through data reduction, data presentation, conclusion drawing, and descriptive qualitative analysis. The research findings show that: (1) Anticipatory Efforts: BPBD formed a Rapid Response Team (TRC) to accelerate disaster management for events such as droughts, volcanic eruptions, tsunamis, and landslides. TRC is responsible for identifying damage, mapping affected areas, rescuing victims, and effectively distributing aid. However, limitations in disaster signage and lack of public education hinder community preparedness. Therefore, awareness needs to be increased through the provision of signage, evacuation routes, socialization, and regular training. Challenges related to funding, expertise, and coordination must also be addressed through careful planning and cross-sector collaboration to ensure effective disaster mitigation and recovery. (2) Responsive Efforts: BPBD enhances disaster preparedness by providing logistics warehouses stocked with food, medicine, clothing, emergency equipment, and evacuation tools such as boats and fire trucks. Aid distribution is coordinated with the military (TNI), police (Polri), and community organizations. BPBD also prepares gathering points, safe evacuation routes, and evacuation posts. Post-disaster recovery involves BPBD, the Public Works and Spatial Planning Agency (PUPR), PLN, the Communications and Information Agency (Kominfo), and the community to repair infrastructure, healthcare facilities, education services, and support economic and housing recovery, aiming to build long-term resilience. Based on the analysis, the author concludes that BPBD has played a significant role in disaster management in Lembata Regency. This achievement stems from both anticipatory and responsive efforts.